AN ANALYSIS OF TRANSLATION METHOD IN WEBTOON FLAWLESS FROM INDONESIAN TO ENGLISH - Istiqomah, Nurul Yogpa; Siahaan, Safnidar (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2023)
This study was conducted to identify the translation methods used by the translator in translating Webtoon Flawles. It is also aimed to find out the most used translation methods in translating Webtoon Flawless from the Indonesian to English. The analysis of translation methods in this study is focused on the translation of the dialogue sentences in Webtoon Flawless. This study applied qualitative method. Qualitative method is applied because the data of this research are in the form of words, phrases, and sentences. The data of this research are taken from Webtoon Flawless from the Indonesian original version and its English translation. The data were analyzed by comparing the Indonesian and its English translation. The result of the study showed that (1) there were 604 data of the dialogues, (2) six methods were used to translate Webtoon Flawless into English; these include word-for-word translation, literal translation, semantic translation, free translation, idiomatic translation, and communicative translation, (3) the most translation method used was free translation method.